Ionization induced by protons on isolated molecules of adenine: theory, modelling and experiment - Champion, C. (2014)
We here report a comparison between semi-empirical and theoretical predictions in terms of differential and total cross sections for proton-induced ionization of isolated adenine molecules. Whereas the first ones are provided by existing analytical models, the second ones are based on two quantum-mechanical models recently developed within the 1st Born and the continuum distorted wave approximation, respectively. Besides, a large set of experimental data is also reported for comparisons. In all kinematical conditions here investigated, we have observed a very good agreement between theory and experiment whereas strong discrepancies were reported with the semi-empirical models in particular when doubly-differential cross sections are analysed.